Quasi-z-source inverter for photovoltaic power gene ration systems - Pravin P. Kalubarme; Prof. Santhosh Kompelli (International Journal of Innovations in Engineering Research and Technology, 2021)
The Z-Source Inverter (ZSI) has been reported suitable for res idential PV system because of the capability of voltage boost and inversion in a single stage. Recently, four new topol ogies, the quasi-Z-Source Inverters (qZSI), have been derived from the original ZSI. This project ana lyzes one voltage fed topology of these four in detail and applies it to PV power generation systems. By using the new quasi-Z-Source topology, the inverter draws a constant current from the PV array and is capabl e of handling a wide input voltage range. It also features lower component ratings and reduced source stress compared to the traditional ZSI. A prototype which provides three phase 50-Hz, 230Vrms ac has been built in laboratory . It is demonstrated from the theoretical analysis and MATLAB/SIMULATION results that t he proposed qZSI can realize voltage buck or boost and dc-ac inversion in a single stage with high reliability and efficiency, which makes it well suited for PV power systems.